Differences in Optic Nerve Head Blood Flow Regulation in Normal Tension Glaucoma Patients and Healthy Controls as Assessed With Laser Speckle Flowgraphy During the Water Drinking Test. Issue 7 (July 2019) - Mursch-Edlmayr, Anna S.; Luft, Nikolaus; Podkowinski, Dominika; Ring, Michael; Schmetterer, Leopold; Bolz, Matthias
Abstract : Précis: Optic nerve head (ONH) perfusion was not significantly altered in subjects with normal tension glaucoma (NTG) nor in healthy individuals after performing the water drinking test (WDT), because of its limited effect on ocular perfusion pressure (OPP). Purpose: ONH blood flow can be maintained stable in healthy individuals because of a physiological phenomenon called autoregulation. Impairment of autoregulation has been shown especially under condition of NTG. The purpose of this study was to investigate the ONH blood flow autoregulation in patients with NTG by influencing the OPP with the WDT. Methods: The study included 9 eyes from 9 white patients with a diagnosis of NTG and 9 eyes from age-matched and sex-matched healthy individuals. In the glaucoma group, the antiglaucomatous therapy was paused 3 weeks before the investigations. Measurements of ONH blood flow were performed with laser speckle flowgraphy. After baseline measurements, individuals ingested 800 mL of water in <5 minutes. Measurements were repeated after 15, 30, and 45 minutes. Results: The water ingestion led to a significant rise in intraocular pressure ( P <0.001) but also mean arterial pressure ( P <0.001) in both groups. This resulted in stable OPP ( P =0.051) with no significant difference between the groups ( P =0.43). ONH blood flow remained stable over time in both groups ( P =0.719). No significant interaction of time and group was shown for all parameters. Conclusions: Our findings show that the WDT does not significantly influence the OPP and therefore has to be considered inferior to other methods used to assess blood flow autoregulation.